2011
DOI: 10.1007/s11060-010-0518-9
|View full text |Cite
|
Sign up to set email alerts
|

Morphine facilitates doxorubicin penetration in the central nervous system: a new prospect for therapy of brain tumors

Abstract: Doxorubicin (DOX) is an anthracycline antibiotic produced by Streptomyces peucetius which interferes with DNA and RNA synthesis by inhibiting topoisomerase II. This drug is used in the treatment of a wide variety of tumors such as carcinomas, sarcomas, leukemias and lymphomas. Clinical trials have, however, demonstrated very limited efficacy in the treatment of brain tumors, due to inefficient accumulation in the brain parenchyma [1]. In fact, DOX is a substrate of the MDR1 isoform of P-glycoprotein (P-gp) eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The first step experiment was then performed combining TMZ treatment (1,77 mg/kg) with morphine (10 mg/kg) [ 16 – 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first step experiment was then performed combining TMZ treatment (1,77 mg/kg) with morphine (10 mg/kg) [ 16 – 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Basing on literature data regarding the pharmacological modulation of BBB by morphine [ 17 ], the most commonly used opioid in oncological patients, we have recently demonstrated that this agent is able to increase delivery and efficacy of doxorubicin (Dox) in animal models, without increasing systemic toxicities [ 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The observation that BBB breakdown is transient and thus resembles an agonist-driven (or therapeutic) opening of the BBB, suggests that METH and related compounds could be used to enhance the transport of other drugs to the CNS. Indeed, this is an idea proposed as early as 2007 (Kast, 2007 ) and, given that METH is FDA approved, has been picked up repeatedly since (Focosi and Kast, 2010 ; Sardi, 2011 ; Capeloa et al, 2014 ). However, preclinical or clinical data in support of such a therapeutic strategy have not yet been reported.…”
Section: Exploiting Meth For Delivering Therapeutics To the Cnsmentioning
confidence: 99%
“…facilitates the delivery of the anticancer agent into the brain, in absence of signs of increased acute systemic toxicity. A quantitative analysis of DOX was performed by LC-MS/MS mass spectrometry; the mean concentration of DOX in the cerebral hemispheres of rodents receiving DOX alone was 5.88±0.34 ng/g fresh tissue versus 18.8±1.01 ng/g fresh tissue in those treated with DOX plus Morph [65, 66]. Thus, it is conceivable that Morph competing with the efflux transporters localized on BBB could increase the access of DOX to the brain [67].…”
Section: Resultsmentioning
confidence: 99%